Analysing the Attitude of Athletes in Tennis Game Performance in Iraq - Taha Al Hiali; Ali Salman; Murtada Sultan Al-Issa; Zaid Hilal Abed Alqiraishi; Arif Ebrahim; Imad Ibrahim Dawood; Ali Falah Mohamed; Hussam abdali abdulridui; Abdul Razzaq Jaber Al Majidi; Gilan Haider Hadi; Israa Abed Jawad, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The purpose of this study was to assess the correlation between athletes' attitudes towards rules, opponents, and dangerous acts, and the game performance of tennis players in Iraq. The study focused on the population of Iraq due to the numerous challenges faced by tennis players in Iraq that directly impacted their game performance. Data from 99 tennis players in Iraq was collected for analysis in this research. The statistical package for social sciences (SPSS) 29 was used to measure the results of Spearman's correlation, model summary, analysis of variance (ANOVA), and coefficients. The research findings indicate that players' attitudes towards rules and opponents have no significant impact on their game performance. However, the study revealed a noteworthy correlation between players' attitudes towards injurious acts and their game performance. In line with the findings, the study indicates that the mental well-being of athletes plays a significant role in influencing their attitudes towards rules and opponents in a positive manner. However, it does not have an impact on the correlation between athletes' attitudes towards injurious acts and their performance in the game. The study made significant contributions to both theoretical and practical aspects of the existing body of knowledge.